Evolution of opsin expression in birds driven by sexual selection and habitat - Bloch, Natasha I. (Proc Biol Sci, 2015)
Theories of sexual and natural selection predict coevolution of visual perception with conspecific colour and/or the light environment animals occupy. One way to test these theories is to focus on the visual system, which can be achieved by studying the opsin-based visual pigments that mediate vision. Birds vary greatly in colour, but opsin gene coding sequences and associated visual pigment spectral sensitivities are known to be rather invariant across birds. Here, I studied expression of the four cone opsin genes (Lws, Rh2, Sws2 and Sws1) in 16 species of New World warblers (Parulidae). I found levels of opsin expression vary both across species and between the sexes. Across species, female, but not male Sws2 expression is associated with an index of sexual selection, plumage dichromatism. This fits predictions of classic sexual selection models, in which the sensory system changes in females, presumably impacting female preference, and co-evolves with male plumage. Expression of the opsins at the extremes of the light spectrum, Lws and Uvs, correlates with the inferred light environment occupied by the different species. Unlike opsin spectral tuning, regulation of opsin gene expression allows for fast adaptive evolution of the visual system in response to natural and sexual selection, and in particular, sex-specific selection pressures.